UNVEILING EDUCATORS INSIGHTS: A COMPREHENSIVE EXAMINATION OF ONLINE PEDAGOGY AT THE SECONDARY LEVEL - Kandpal, Ritu; Mehrotra, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of technology in education has led to a paradigm shift, particularly evident in the ascendancy of online pedagogy at the secondary level. This research paper unveils educator’s insights, offering a comprehensive examination of the challenges, opportunities, and best practices associated with the implementation of online teaching methods. Educators navigate technological barriers and pedagogical adaptations, providing nuanced perspectives on the intricacies of virtual education. Opportunities abound as online pedagogy transcends geographical constraints, enhances learning through multimedia resources, and enables personalized learning experiences. Best practices, encompassing effective communication, clear instructions, and dynamic content creation, emerge as crucial elements for success. The establishment of virtual communities within online classrooms fosters engagement and motivation. This study contributes valuable insights to the discourse on educational transformation, guiding educators, policymakers, and stakeholders in understanding the multifaceted landscape of online teaching methods in secondary education.